(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
NBFCs play salient role in culverting scarce financial resources in capital formation. They supplement the role of traditional banks by meeting the financial needs of organized and unorganized sector. The fill the credit gaps where the reach of banks is minimal. In this paper, the scope for NBFCs is examined along with challenges faced by them. They have a cutting edge over banks in serving MSMEs and unorganized sector because of customized product offerings. Digital technology has created a new arena of growth. The degrading assets quality, decreased profitability due to increased provisioning still remain challenge. The study is concluded by giving recommendation on how the efficiency of NBFCs can be increased. Creating a risk evaluating mechanism and prudent credit monitoring system can bring financial stability and protect interest of depositors.